Effects of tempering on internal friction of carbon steels - Hoyos, J. J. (2011)
Two steels containing 0.626 and 0.71 wt.% carbon have been studied to determine the effects of tempering on the microstructure and the internal friction. The steels were annealed at 1093 K, quenched into water and tempered for 60 min at 423 K, 573K and 723 K. The increase of the tempering time diminishes the martensite tetragonality due to the redistribution of carbon atoms from octahedrical interstitial sites to dislocations. Internal friction spectrum is decomposed into five peaks and an exponential background, which are attributed to the carbide precipitation and the dislocation relaxation process. Simultaneous presence of peaks P1 and P2 indicates the interaction of dislocations with the segregated carbon and carbide precipitate.